Autocrine stimulation of interleukin 1 beta in acute myelogenous leukemia cells (The Rockefeller University Press, 1987)
A significant increase in CD25 antigen-positive cells by IL-1 was observed in cells of a patient with M7 acute myelogenous leukemia. Basal proliferation and expression of CD25 antigen by the M7 leukemic cells were inhibited by addition of anti-IL-1 beta antibody in a dose- dependent manner, but not by rabbit anti-IL-1 alpha antibody. Culture supernatants of these leukemic cells contained IL-1 activity, which was specifically inhibited by addition of anti-IL-1 beta antibody, and Northern blot analysis detected intracellular IL-1 beta mRNA. These results indicated that autocrine secretion of IL-1 beta was involved in proliferation of some myelogenous leukemic cells.